CULTURE, ITS DIMENSIONS AND IMPLICATIONS TO THE TEACHING OF ENGLISH - Rusdi, Rusdi (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2016)
Culture is an important aspect in learning a foreign language. This paper discusses three main conceptual issues: the concept of culture, its dimensions, and its implication to the teaching of English. In a broader sense, culture umbrellas arts, music, literary works, scientific findings, and other human beingsâ€™ creations. In a narrower sense, culture covers habits, customs, and social behaviours of a society. Four cultural dimensions: individualism, collectivism, high-context, and low-context are discussed. Deductive and inductive methods of reasoning are also discussed. In context of the teaching of English, culture is classified into local culture, foreign culture, and academic culture. Local culture refers to values and norms shared by the students who learn English as a foreign language. Foreign culture is the beliefs, norms, and values of the target language. Academic culture is the norms and values practiced in academic life. This paper strongly argues that the teaching of English as a foreign language should be based on local cultural values and norms. Language functions to express thoughts and culture. Therefore, English is used as an instrument to express thoughts and culture of learners who learn English.Â Keyword: culture, English language teaching, academic culture.